Non-Gaussianity and the induced gravitational wave background. Issue 10 (27th October 2021) - Adshead, Peter; Lozanov, Kaloian D.; Weiner, Zachary J.
Abstract: Scalar metric fluctuations generically source a spectrum of gravitational waves at second order in perturbation theory, poising gravitational wave experiments as potentially powerful probes of the small-scale curvature power spectrum. We perform a detailed study of the imprint of primordial non-Gaussianity on these induced gravitational waves, emphasizing the role of both the disconnected and connected components of the primoridal trispectrum. Specializing to local-type non-Gaussianity, we numerically compute all contributions and present results for a variety of enhanced primordial curvature power spectra.